How post-saccadic target blanking affects the detection of stimulus displacements across saccades - Irwin, David E.; Robinson, Maria M. (Vision research (Oxford), 2018)
When a visual stimulus is displaced during a saccade the displacement is often not noticed unless it is large compared to the amplitude of the eye movement. Displacement detection is improved, however, if a blank intervenes between saccade target offset and the presentation of the displaced post-saccadic stimulus. This has been interpreted as evidence that precise information about eye position and accurate memory for the position of the pre-saccadic target are available immediately after saccade offset, but are overridden by the presence of the post-saccadic stimulus if it is present when the eyes land. In the current set of experiments we examined in more detail how blanking contributes to the increase in displacement sensitivity. In two experiments we showed that the presentation of a blank interval between saccade offset and the presentation of the displaced stimulus improved people’s ability to detect that the stimulus had been displaced and also their ability to judge the direction that it had been displaced, but only for displacements opposite to the direction of the saccade (backward displacements). A third experiment suggested that this improvement in the detection of backward displacements was due in part to subjects misremembering the saccade target location as being closer to the initial fixation point than it actually was immediately after the saccade but remembering its location more veridically 50 ms later. This has the effect of improving the detection of displacements as well as their direction of displacement, but preferentially for backwards vs. forward displacements.